Earth Block Construction in Nepal as Alternative to Reconstruction after the 2015 Gorkha Earthquake - Kasajoo, Aayush; Hongwang, Ma (Journal of the Institute of Engineering, 2018)
On April 25, 2015, 7.8 magnitude earthquake occurred in Central Nepal with epicentre in Gorkha District at 11:56 NST (local time). A major aftershock of magnitude 7.3 on May 12, 2015 resulted in enhancement of damages. Almost 800,000 buildings were fully or partially damaged. This paper highlights the different types of buildings in Nepal and the damage patterns recorded from the earthquake. Different causes of failures are highlighted for different types of building including masonry, wooden, reinforced cement concrete etc. 44.2% of the buildings in Nepal are masonry type which in fact performed the worst during the earthquake. One of the main reason was the poor quality of bricks used in the buildings. Most of the masonry buildings in Nepal are located in the rural areas where the economic condition of people are not up to the level. Utilization of local resources and people skill is important. Thus, as an alternative to it, we have put forward the idea of earth block construction which is not only earthquake resillient but lighter, greener sustainable and economical. Journal of the Institute of Engineering, 2018, 14(1): 64-74